Clinical, economic and organizational impact of pharmacist interventions on injectable antineoplastic prescriptions: a prospective observational study - Céline Zecchini; Thi-Ha Vo; Sébastien Chanoine; Marion Lepelley; Mathieu Laramas; Aude Lemoigne; Benoît Allenet; Isabelle Federspiel; Pierrick Bedouch (BMC, 2020)
Abstract Background Pharmacists play a key role in ensuring the safe use of injectable antineoplastics, which are considered as high-alert medications. Pharmaceutical analysis of injectable antineoplastic prescriptions aims to detect and prevent drug related problems by proposing pharmacist interventions (PI). The impact of this activity for patients, healthcare facilities and other health professionals is not completely known. This study aimed at describing the clinical, economic, and organizational impacts of PIs performed by pharmacists in a chemotherapy preparation unit. Methods A prospective 10-week study was conducted on PIs involving injectable antineoplastic prescriptions. Each PI was assessed by one of the four multidisciplinary expert committees using a multidimensional tool with three independent dimensions: clinical, economic and organizational. An ancillary quantitative evaluation of drug cost savings was conducted. Results Overall, 185 patients were included (mean age: 63.5 ± 13.7 years; 54.1% were male) and 237 PIs concerning 10.1% prescriptions were recorded. Twenty one PIs (8.9%) had major clinical impact (ie: prevented hospitalization or permanent disability), 49 PIs (20.7%) had moderate clinical impact (ie: prevented harm that would have required further monitoring/treatment), 62 PIs (26.2%) had minor clinical impact, 95 PIs (40.0%) had no clinical impact, and 9 PIs (3.8%) had a negative clinical impact. For one PI (0.4%) the clinical impact was not determined due to insufficient information. Regarding organizational impact, 67.5% PIs had a positive impact on patient management from the healthcare providers' perspective. A positive economic impact was observed for 105 PIs (44.3%), leading to a saving in direct drug costs of 15,096 €; 38 PIs (16.0%) had a negative economic impact, increasing the direct drug cost by 11,878 €. Overall cost saving was 3218€. Conclusions PIs are associated with positive clinical, economic and organizational impacts. This study confirms the benefit of pharmacist analysis of injectable antineoplastic prescriptions for patient safety with an overall benefit to the healthcare system.